Hadith #4875 - Sunan Abi Dawud - Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Amr bin Abi Salmah عمرو بن أبي سلمة التنيسي; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
I said to the Prophet (ﷺ): It is enough for you in Safiyyah that she is such and such (the other version than Musaddad’s has:) meaning that she was short-statured. He replied; You have said a word which would change the sea if it were mixed in it. She said: I imitated a man before him (out of disgrace). He said: I do not like that I imitate anyone even if I should get such and such.
Grade: Sahih